The ‘hangar of the future’ for sustainable aviation - Plastropoulos, Angelos; Fan, Ip-Shing; Avdelidis, Nicolas P.; Angus, Jim; Maggiore, John; Atkinson, Helen (Cambridge University Press (CUP), 2024)
Sustainability is becoming a major strategic driver within the aviation industry, which has moved from providing primarily economic benefits to delivering the ‘triple bottom line’, including social and environmental impact as well as financial performance. Sustainable aviation is also being tracked by the International Civil Aviation Organisation (ICAO) Global Collation for Sustainable Aviation. Operations and Infrastructure is an important near-term opportunity to deliver sustainability benefits. Digital Technologies, Integrated Vehicle Health Management (IVHM) and Maintenance Repair and Overhaul (MRO) play a prominent role in implementing these benefits, with a particular focus on operational efficiencies. As part of this, the sustainable smart hangar of the future is a concept that is becoming more and more important in forming the future of the aviation industry. The Hangar of the Future is an excellent opportunity for innovation, combining the progress in manufacturing, materials, robotics and artificial intelligence technologies. Succeeding in developing a hangar with these characteristics will provide us with potential benefits ranging from reduced downtime and costs to improved safety and environmental impact. This work explores some of the key features related to the sustainable smart hangar of the future by discussing research that takes place in DARTeC’s (Digital Aviation Research and Technology Centre) hangar led by the IVHM Centre in Cranfield. Additionally, the paper touches on some longer-term aspirations.
Keywords: smart hangar; hangar of the future; aircraft maintenance; MRO; IVHM; Industry 4.0; Industry 5.0; NDT; robotics; 40 Engineering; 3505 Human Resources and Industrial Relations; 35 Commerce, Management, Tourism and Services; Aerospace & Aeronautics